PERFORMANCE OF FRP COMPOSITE PLATES UNDER BALLISTIC IMPACT: EXPERIMENTAL INVESTIGATION BASED ON NIJ 0108.01 AND MESO-SCALE NUMERICAL MODEL DEVELOPMENT - Ezekiel Halor Jatmiko, Fito
The increasing demand for effective ballistic protection systems in military and aerospace industries has led to extensive research on the performance of fiber-reinforced polymer (FRP) composite plates under high-velocity impact. This study aims to investigate the ballistic response of FRP plates through experimental analysis based on the National Institute of Justice (NIJ) standards and the concurrent development of a meso-scale numerical model. Experimental and numerical approaches are both used to complement each other to ensure reliable, repeatable, and optimizable method for other researches in the future. The ballistic impact experiments follow NIJ 0108.01 standards, where protective specimen plates are exposed to impacts from a Type II ballistic threat: five shots of 9 mm Full Metal Jacket Round Nose (FMJ RN) bullets weighing 8 grams and moving at 358±12 m/s. The experiments were successfully done on three thick one hundred plies composite plate specimens with three variation of fiber types: carbon, glass, and Kevlar. The specimens were manufactured by the hand-layup and vacuum bagging curing method and has successfully passed the Type II NIJ 0108.01 tests, resulting only in partial penetrations, with penetration depths of 11.10%, 9.95%, and 22.22% for the carbon, glass, and Kevlar reinforced fiber composite respectively. A meso-scale preliminary numerical model was also developed in nonlinear explicit software LS-DYNA. Composite plates were modelled as stacked shell element plates. Intralayer damage definition was defined with the Enhanced Composite Damage and Laminated Composite Fabric model with Chang-Chang and Hashin failure criterion respectively. Interlayer damage was defined by a tiebreak contact and the projectile was modelled as both a rigid and a deformable strain-rate Modified Johnson-Cook model, and lastly interaction between projectile and target were defined with erosion contacts. The described modelling method were validated to a referenced paper and resulted in an error of 5.9%. Comparison between the modelling method and the NIJ 0108.01 experiments showed good agreement in ballistic performance with penetration depth of 10% and full energy absorption when a deformable projectile, refined mesh, and Laminated Composite Fabric material model was used. Further refinement of the numerical model was then proposed.